Application of computed tomography dose index as dosimetric parameter in dental tomography - MAURO,Rodrigo Antonio Pereira (2021)
ABSTRACT Objective Quantify the CTDI from a reference beam, correcting this value for several beam widths from the ratio of CTDI100 values measured in the air, and verifying the underestimation of the dose comparing CTDI100 and CTDI300, applied to dental CBCT. Methods i-CAT and Prexion 3D tomographs, 100mm pencil ionization chamber, electrometer. Firstly for beam above 40 mm, CTDIW,NT from CTDIW,Ref, multiplied by the ratio of CTDIAR measurements to N.T widths and reference, was estimated. In second, CTDI100 and CTDI300 are obtained by displacing the ionization chamber along the beam with spacing intervals equal to 100 mm to cover sufficiently large integration intervals for CBCT protocols, and a comparison is made through the modified efficiency. Results CTDIAR,100,Ref averaged 53% higher than CTDIW,Ref, due to attenuation of the beam by the simulator object, and the ratio between CTDIAR,100,Ref and CTDIW,Ref is greater than 1, being this constant relationship and validating the method for dosimetry in quality control tests. For the second method, CTDI100 greatly underestimates the dose deposited on the central axis, where CTDI300 covers all beam sizes and stands out in relation to CTDI100 to more accurately quantify the radiation levels emitted. Conclusions The IEC method is applicable to quality control, facilitating practice, and optimizing time and resources. CTDI300 is a better dose descriptor than CTDI100, and should be implemented for CBCT modalities when used.